2014
DOI: 10.4028/www.scientific.net/amm.663.322
|View full text |Cite
|
Sign up to set email alerts
|

Twin Pulsating Jets Impingement Heat Transfer for Fuel Preheating in Automotives

Abstract: The problem of environmental pollution and depletion of fossil fuel can be reduced in automotives by using an alternative bio-fuel and improve the ignition process in engine. Both solutions need to use the fuel preheating technique. This work presents the idea of fuel preheating by using exhaust impingement on the fuel tank. Heat transfer between twin pulsating hot air jets and flat copper target was investigated as an application for preheating of automotive fuel to improve ignition process in the engine. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
(16 reference statements)
1
2
0
Order By: Relevance
“…There was a consistency in the results for the heat transfer rate for the surface coated by TiO 2 solution in the most cases compared to other results like [68,70,71] as shown in Figure 23. There is a significant improvement in the result of Nusselt number as against other results such as [29,[66][67][68][69]. There was a consistency in the results for the heat transfer rate for the surface coated by TiO2 solution in the most cases compared to other results like [68,70,71] as shown in Figure 23.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…There was a consistency in the results for the heat transfer rate for the surface coated by TiO 2 solution in the most cases compared to other results like [68,70,71] as shown in Figure 23. There is a significant improvement in the result of Nusselt number as against other results such as [29,[66][67][68][69]. There was a consistency in the results for the heat transfer rate for the surface coated by TiO2 solution in the most cases compared to other results like [68,70,71] as shown in Figure 23.…”
Section: Discussionsupporting
confidence: 57%
“…This article presented and discussed the results of the study about the impact of nanocoating concentration on the heat transfer enhancement within the interference zone of the twin impingement jets mechanism. The manuscript presented the application of RSM There is a significant improvement in the result of Nusselt number as against other results such as [29,[66][67][68][69]. There was a consistency in the results for the heat transfer rate for the surface coated by TiO 2 solution in the most cases compared to other results like [68,70,71] as shown in Figure 23.…”
Section: Discussionmentioning
confidence: 70%
“…Earlier studies indicated that the steady single jet generated a better heat transfer rate compared to that of the pulsating jet at the stagnation point [37]. A velocity increment was noted at the center line of the interference zone, wherein an increasing velocity led to an enhanced heat transfer and a higher Nusselt number [37,38,39,40,41]. Table 2 illustrates the enhancement ratio of the TiO 2- nanocoated surface plate in different models.…”
Section: Resultsmentioning
confidence: 98%